Plasma leptin levels are not affected by commonly used anti-hypertensive drugs in patients with essential hypertension - Canatan, H; Bakan, I; Akbulut, M; Halifeoglu, I; Baydas, G (Federation Amer Soc Exp Biol, 2004)
[Abstract Not Available]
Experimental Biology 2004 Meeting -- APR 17-21, 2004 -- Washington, DC